Spectrum cap and firms' performance: Thailand's experience - Pratompong Srinuan; Thunwar Phansatarn; Chalita Srinuan (International Telecommunications Society (ITS), 2018)
Spectrum auction has been accepted as an efficient tool for allocating the radio spectrum and increasing competition level among service providers in the telecommunication market. Most of National Regulatory Authorities (NRAs) use spectrum cap as an incentive instrument to facilitate new entrants and to reduce a chance of natural monopoly in acquiring spectrum. These two different regulatory instruments seem to provide contradictory results. On one hand spectrum auction should allow Mobile Network Operator (MNO) to obtain as much as spectrum bandwidth. It may lead to one MNO may gain most of spectrum bandwidth in the market or being a dominant player in the market. On another, spectrum cap limits amount of bandwidths where the MNO could obtain. It aims to provide an opportunity to smaller and/or new comer operator to gain spectrum bandwidths as well as its competitive advantage. The National Broadcasting and Telecommunications Commission (NBTC) has followed the practices from other NRAs by implementing spectrum auctions together with setting spectrum cap for each bidder in an event of auction. This paper aims to investigate impact on firms' performance, i.e. data share to spectrum share ratio, subscriber share to spectrum share ratio, etc., in Thailand. The findings show that 40% sub-1GHz cap produces a better output in term of spectrum efficiency. It is somehow contrast with other studies. However, this may result from a long term implementation of spectrum cap. Mobile operator needs to prepare itself to handle the limitation of spectrum.
Keywords: 330; Spectrum cap; Firms' performance; Thailand